High and dry: Systematic wetland drying degrades North American habitat network supporting breeding white-faced ibisFigshareFigshare - Shea P. Coons; Victoria J. Dreitz; J. Patrick Donnelly (Global Ecology and Conservation, 2025)
Wetlands structure landscape biodiversity by providing habitat to numerous fish and wildlife species. However, many migratory waterbird species, including the white-faced ibis (Plegadis chihi; hereafter ‘ibis’), face threats from climate change, increasing human populations, and shifting land use practices, which are altering wetland ecosystems. Using ibis breeding colony surveys, we identified 153 wetland complexes to indicate the status of an ecologically diverse wetland network inclusive of private and public wetland resources. We assessed long-term (1988–2020) surface water trends within individual wetland complexes and by region. We also examined changes to surface water based on land ownership, hydroperiod, and wetland class. To identify landscape drivers influencing flooding patterns, we linked long-term trends to regional climate and anthropogenic factors. Approximately 60 % of wetland complexes experienced significant declines in surface water. Despite substantial interannual variability, overall losses were significant in five of eight regions examined. Drying reduced wetland availability on public wildlife refuges, which support important over-water nesting sites for ibis colonies, by 13–27 %, while foraging resources provided by adjacent flood-irrigated agriculture declined by 15–35 %. Changing snowpack, temperatures, and agricultural irrigation practices were prevalent drivers of wetland declines. To accelerate wetland network protections, we developed an interactive web application (https://sheacoons.users.earthengine.app/view/wet-wfib-beta-11) that makes our data directly available to managers to reduce uncertainties in management decisions. Our findings underscore a need for management strategies that sustain the wetland habitats ibis and other migratory waterbirds rely upon.